Synthesis and characterizaton of polyamidoamine dendrimer nanopolymers - Phairat Punyacharoennon (Chulalongkorn University, 2010)
The PAMAM dendrimers were synthesized by consecutively repeating two reactions; Michael addition and Amidation to produce amine terminated product. The FTIR, 1H and 13C-NMR analysis were employed to follow the synthesis reaction. In separate work, grafting of hyperbranched PAMAM polymers onto ultrafine silica followed by functionalization via the introduction of phosphonic acid groups into the branch ends was performed. First, an initiating site was incorporated into the silica surface by reacting the silica silanol group with 3-aminopropyltriethoxysilane, producing amino functionalized silica. The free amine group content was altered by varying the ratio of methanol to water in the hydrolysis step of the silanization reaction. Grafting of PAMAM was attained by three rounds of sequential Michael addition of silica amino groups to methyl acrylate and amidation of the resulting terminal methyl ester groups with ethylenediamine. Completion of the grafting reaction in each step was clearly confirmed using FTIR analysis. However, the amino group content determined in each step was found to be significantly lower than theoretically expected, perhaps indicative of side reactions and, in later stages, steric hindrance. The PAMAM dendrimers and hyperbranched PAMAM grafted silica were functionalized by a Mannich type reaction to phosphorylate the terminal amino groups, producing the phosphorylated PAMAM dendrimers and phosphorylated hyperbranched PAMAM grafted silica. Then they were applied on cotton fabric to produce flame-retardant cellulose. The two synthesized products showed flame retardancy effect on cotton fabric. After washing test, the phosphorylated hyperbranched PAMAM grafted silica showed better retention of fire retardancy than phosphorylated PAMAM dendrimers, indicating its wash-off resistancy performance. In addition, the bursting strength of phosphorylated PAMAM dendrimers finished cotton was worst than phosphorylated hyperbranched PAMAM grafted silica finished cotton. This might be due to the effect of more phosphonic acid groups content of phosphorylated PAMAM dendrimers. As a result, its higher acidicity accelerated the thermal degradation of cotton fabric during fixation of phosphorylated PAMAM dendrimers.